Yeast Biotechnology 3.0 - Willaert, Ronnie G. (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Yeasts are truly fascinating microorganisms. Due to their diverse and dynamic activities, they have been used for the production of many interesting products, such as beer, wine, bread, biofuels and biopharmaceuticals. Saccharomyces cerevisiae (bakers' yeast) is the yeast species that is surely the most exploited by man. Saccharomyces is a top choice organism for industrial applications, although its use for producing beer dates back to at least the 6th millennium BC. Bakers' yeast has been a cornerstone of modern biotechnology, enabling the development of efficient production processes for antibiotics, biopharmaceuticals, technical enzymes, and ethanol and biofuels. Today, diverse yeast species are explored for industrial applications, such as e.g. Saccharomyces species, Pichia pastoris and other Pichia species, Kluyveromyces marxianus, Hansenula polymorpha, Yarrowia lipolytica, Candida species, Phaffia rhodozyma, wild yeasts for beer brewing, etc. This Special Issue is focused on recent developments of yeast biotechnology with topics including recent techniques for characterizing yeast and their physiology (including omics and nanobiotechnology techniques), methods to adapt industrial strains (including metabolic, synthetic and evolutionary engineering) and the use of yeasts as microbial cell factories to produce biopharmaceuticals, enzymes, alcohols, organic acids, flavours and fine chemicals, and advances in yeast fermentation technology and industrial fermentation processes.